A fibre optic angle sensing tape for applications in robotics and automation - Pillai, Sivaji; Charrett, Thomas O. H.; Kissinger, Thomas; James, Stephen W.; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2023)
A dual-fibre single-plane angle-sensing tape that utilizes optical Fibre Segment Interferometry and Range- Resolved Interferometry (RRI) for angle sensing is presented. The sensing tape facilitates the multiplexing of an array of angle sensors along its length and can be retrofitted into small robots and construction equipment. We demonstrate its application on three non-rotational joints of a small five-axis robot, describing the design, construction, measurement principle, and presenting measurement results. Preliminary data shows that the angles measured by the sensing tape exhibited agreement within a range of ±0.005° with the manufacturer-installed angle encoder of the robot.
Keywords: Angle sensing tape; Fiber Segment interferometry